Aspirin plus verapamil relieves angina and perfusion abnormalities in patients with coronary microvascular dysfunction and Chagas disease: a pilot non-randomized study - Pavão,Rafael Brolio (2021)
Abstract INTRODUCTION: Most patients with chronic cardiomyopathy of Chagas disease (CCCD) harbor a secondary cause of coronary microvascular dysfunction (CMD), for which there is no evidence-based therapy. We evaluated the impact of verapamil plus aspirin on symptoms and perfusion abnormalities in patients with CCCD and CMD. METHODS: Consecutive patients with angina pectoris, who had neither coronary artery obstructions nor moderate-severe left ventricular dysfunction (left ventricular ejection fraction > 40%) despite showing wall motion abnormalities on ventriculography, were referred for invasive angiography and tested for Chagas disease. Thirty-two patients with confirmed CCCD and ischemia on stress-rest SPECT myocardial perfusion scintigraphy (MPS) were included. Clinical evaluation, quality of life (EQ-5D/ Seattle Angina Questionnaire), and MPS were assessed before and after 3 months of treatment with oral verapamil plus aspirin (n=26) or placebo (n=6). RESULTS: The mean patient age was 64 years, and 18 (56%) were female. The ischemic index summed difference score (SDS) in MPS was significantly reduced by 55.6% after aspirin+verapamil treatment. A decrease in SDS was observed in 20 (77%) participants, and in 10 participants, no more ischemia could be detected. Enhancements in quality of life were also detected. No change in symptoms or MPS was observed in the placebo group. CONCLUSIONS: This low-cost 3-month treatment for patients diagnosed with CCCD and CMD was safe and resulted in a 55.6% reduction in ischemic burden, symptomatic improvement, and better quality of life.